(untitled) (Physical Education, Health and Social Sciences, 2025)
Students frequently exhibit forward head posture (FHP), which is linked to headaches, neck pain, and occasionally periocular discomfort. To lessen periocular pain and related symptoms, orthoptic interventions that focus on eye control and eye-neck interaction have been suggested.